A Primary Sequence Analysis of the ARGONAUTE Protein Family in Plants - Rodríguez-Leal, Daniel; Castillo-Cobián, Amanda; Rodríguez-Arévalo, Isaac; Vielle-Calzada, Jean-Philippe (Frontiers in Plant Science, 2016)
Small RNA (sRNA)-mediated gene silencing represents a conserved regulatory mechanism controlling a wide diversity of developmental processes through interactions of sRNAs with proteins of the ARGONAUTE (AGO) family. On the basis of a large phylogenetic analysis that includes 206 AGO genes belonging to 23 plant species, AGO genes group into four clades corresponding to the phylogenetic distribution proposed for the ten family members of Arabidopsis thaliana. A primary analysis of the corresponding protein sequences resulted in 50 sequences of amino acids (blocks) conserved across their linear length. Protein members of the AGO4/6/8/9 and AGO1/10 clades are more conserved than members of the AGO5 and AGO2/3/7 clades. In addition to blocks containing components of the PIWI, PAZ, and DUF1785 domains, members of the AGO2/3/7 and AGO4/6/8/9 clades possess other consensus block sequences that are exclusive of members within these clades, suggesting unforeseen functional specialization revealed by their primary sequence. We also show that AGO proteins of animal and plant kingdoms share linear sequences of blocks that include motifs involved in posttranslational modifications such as those regulating AGO2 in humans and the PIWI protein AUBERGINE in Drosophila. Our results open possibilities for exploring new structural and functional aspects related to the evolution of AGO proteins within the plant kingdom, and their convergence with analogous proteins in mammals and invertebrates.